PAINTINGS THAT REFLECT THE ERA: A REVIEW OF ILYA RIPYN’S WORKS - Kunak , Anna (Collection of scientific papers «ΛΌГOΣ», 2024)
Ilya Ripyn is one of the most prominent figures in Ukrainian and Russian art of the late 19th century. His work goes beyond simple artistic depiction and delves into a deep analysis of national identity, social realities, and cultural processes. In today’s world, which faces numerous challenges related to national identity and cultural conflicts, Ripyn's works take on new relevance. Through his realism, he not only documents the social and political realities of his time but also serves as an important source for researchers trying to understand the complex dynamics and influences on cultural identity.